Trends in fertiliser use and efficiency in the Great Barrier Reef catchment area - Stephen E. Lewis; Cassandra S. James; Zoe T. Bainbridge; Aaron M. Davis; Adam Northey; Emma Lawrence; Rebecca Bartley (Journal of Environmental Management, 2026)

A battleground of climate change: Summer air temperatures in social housing - Sebastian Pfautsch; Agnieszka Wujeska-Klause; Judi R. Walters; Abby Mellick Lopes; Louise Crabtree-Hayes; Emma Power; Bhavya Chitranshi; Helen Armstrong; Katherine Gibson; Cameron Tonkinwise; Stephen Healy (Urban Climate, 2026)

Water quality trends in river catchments draining to the Great Barrier Reef: an analysis of ∼40 years of data - Cassandra S. James; Petra M. Kuhnert; Stephen E. Lewis; Rebecca Bartley; Emma Lawrence; Jennifer Strauss; Reinier M. Mann; Ryan D.R. Turner; Zoe T. Bainbridge (Journal of Environmental Management, 2026)

Evolving perspectives on agricultural systems research: Contemporary trends and editorial directions - Jagadish Timsina; Mark van Wijk; Krishna Devkota; Antonius G.T. Schut; Carlos Parra-López; Guillaume Martin; James A. Turner; Emma Stephens; Adam M. Komarek; Simon Fielke; Leonard Rusinamhodzi; Nadine Andrieu; et al. (Agricultural Systems, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Strategic deep tillage of deep sand soils impacts the sorption and biological availability of trifluralin - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Michael T. Rose; Benedict Arthur; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Resilience, Loneliness, and Mental Well-Being in the UK Farming Community - Sarah Nyczaj Kyle; Stephen Dunne; Emma Barkus (Journal of Agromedicine, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Comparing Influences of Natural and Artificial Woody Habitat on Benthic Macroinvertebrates in a North Temperate Lake - Matthew P. Woo; Thomas M. Detmer; Montana E. Airey; Stephen F. Jane; Dov F. Sax; Evan Dlugos; Emma G. Menard; Julián Torres-Dowdall; Peter B. McIntyre (Hydrobiologia, 2026)
Littoral habitat is an important organizing force in lacustrine food webs. Modification of littoral habitat directly impacts aquatic macroinvertebrates, which are important vectors between basal resources and higher trophic levels. Lakeshore residential development is a pervasive phenomenon often characterized by the loss of coarse woody habitat (CWH) from lakes, and the construction of artificial wooden structures (docks and ramps). To characterize the effects of artificial wooden structures on macroinvertebrate spatial distributions, we surveyed assemblages across a lightly developed lake in New York’s Adirondack Park. Using benthic sweeps and Hester-Dendy samplers, we sampled assemblages at both natural CWH and artificial wooden structures (boat ramps), and compared them to those in adjacent, non-woody areas. We found that both CWH and artificial wooden structures facilitated larger, more complex assemblages than non-woody areas. We additionally considered general shoreline characteristics, and found only compositional effects on assemblages. We suggest that impacts on aquatic macroinvertebrates arise at a fine spatial scale, and find evidence that development-associated CWH loss drives macroinvertebrate depletion. Although CWH and artificial wooden structures are unlikely to be equivalent at whole-lake scales, macroinvertebrate depletion may be functionally alleviated at fine scales by the construction of artificial wooden structures such as ramps.

Development of new global lake brGDGT-temperature calibrations: advances, applications, challenges, and recommendations - Emma J. Pearson; Steve Juggins; Harry Allbrook; Louise C. Foster; Dominic A. Hodgson; B. David A. Naafs; Tony Phillips; Stephen J. Roberts (Quaternary Science Reviews, 2025)

Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

Occurrence and tissue distribution of per- and polyfluoroalkyl substances (PFAS) in fishes from waterbodies with point and non-point sources in Massachusetts, USA - Heather L. Walsh; Vicki S. Blazer; Emma Lord; Stephen T. Hurley; Denis R. LeBlanc (Aquatic Toxicology, 2025)

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Establishment, current status and possible origin of the greater white-toothed shrew Crocidura russula in Great Britain - Graham C. Smith; Ian F. Bond; Terry Coult; Dan Henderson; Courtney Graham; Emma Brand; Allan D. McDevitt; Philip A. Stephens; Sophie Webb; Matt Larsen-Daw (Biological Invasions, 2025)
Great Britain has three native shrews, while the greater white-toothed shrew (GWT: Crocidura russula ) is native to the European continent and some Channel islands. The GWT shrew was first reported in northern England in 2022. We detail its immediate investigation through national authorities, non-government bodies and individuals. Sixteen GWT were among 595 small mammals live-trapped. Barn owl pellet analysis revealed 56 GWT skulls in two areas. Genetic analysis of the cytochrome b gene suggests these population were derived from one or more continental European introductions, but not from the nearby island of Ireland where this non-native species has been present since at least 2007. The overall government response from the Department for Environment, Food and Rural Affairs and Natural England concluded that the species is too widespread to have any reasonable chance of eradication, but there remain ongoing efforts to determine the extent of invasion and its effect on native species.

Twin differences in lateral ventricle size accompany twin differences in phonological decoding - Mark A. Eckert; Kenneth I. Vaden; Emma C. Bartley; Stephen A. Petrill (Brain Structure and Function, 2025)

First documented sighting of a group of bowhead whales outside their typical range in Hudson Bay - Veronica L. M. Coppolaro; Emma L. Ausen; Stephen D. Petersen; Steven H. Ferguson; Marianne Marcoux (Polar Biology, 2025)

The acute effects of continuous and intermittent whole-body passive heating on cardiovascular disease risk indicators in healthy and young males and females - Yunuo Su; Adela Martinkova; Emma O’Donnell; Stephen J. Bailey; Christof A. Leicht (European Journal of Applied Physiology, 2025)
Purpose Heat therapy is recognised to promote cardiovascular health, and whilst most recent heat therapy investigations have focussed on continuous heat exposure, traditional sauna use often includes recovery periods. This study compared the acute effects of continuous versus intermittent whole-body heating on cardiovascular function markers in males and females. Methods Twenty healthy participants (25 ± 3 years; 10 males, 10 females) were exposed to 2 passive heating regimens: continuous heating (CH) for 60 min and intermittent heating (IH) comprised of 3 × 20-min blocks interspersed by 15-min cooling breaks. Skin perfusion, blood pressure (BP), plasma nitrite, interleukins, body temperature, and thermal perceptual responses were assessed. Results Greater increases in rectal temperature (T rec ) (CH: 1.2 ± 0.1 °C; IH: 0.5 ± 0.1 °C), skin perfusion, systolic blood pressure (SBP), heart rate (HR), interleukin-6 (IL-6) and plasma nitrite were found in CH compared to IH ( p ≤ 0.01), but the thermal perceptual response was more unfavourable during CH ( p < 0.01). Females had higher skin perfusion and plasma nitrite concentrations ( p ≤ 0.04), but lower brachial and central BP than males in both conditions ( p ≤ 0.01). Furthermore, females reached a higher T rec and more unfavourable thermal perception in CH ( p ≤ 0.02). Conclusion More pronounced cardiovascular responses were associated with higher T rec and discomfort. Females exhibited higher skin perfusion and plasma nitrite concentrations than males and reported less favourable thermal perception in CH, but not in IH.

“The end point is a… more appropriate innovation ecosystem” Mission-oriented and responsible innovation in Australian agricultural systems - Simon Fielke; Aysha Fleming; Emma Jakku; Cara Stitzlein; Katie Ricketts; Gillian Cornish; Stephen Snow; Graham Bonnett (Agricultural Systems, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effects of microbial alteration of oceanic crust on sulfur cycling in hydrothermal systems - Sarah N. Moriarty; Emma Bertran; James W. Dottin; James Farquhar; David T. Johnston; Stephen J. Piercey; Dennis Sánchez-Mora; Michael G. Babechuk; Jason B. Sylvan; John W. Jamieson (Geochimica et Cosmochimica Acta, 2025)

Nitrogen Availability and Changes in Precipitation Alter Microbially Mediated NO and N 2 O Emissions From a Pinyon–Juniper Dryland - Sharon Zhao; Alexander H. Krichels; Elizah Z. Stephens; Anthony D. Calma; Emma L. Aronson; G. Darrel Jenerette; Marko J. Spasojevic; Joshua P. Schimel; Erin J. Hanan; Peter M. Homyak (Global Change Biology, 2025)
Climate change is altering precipitation regimes that control nitrogen (N) cycling in terrestrial ecosystems. In ecosystems exposed to frequent drought, N can accumulate in soils as they dry, stimulating the emission of both nitric oxide (NO; an air pollutant at high concentrations) and nitrous oxide (N 2 O; a powerful greenhouse gas) when the dry soils wet up. Because changes in both N availability and soil moisture can alter the capacity of nitrifying organisms such as ammonia‐oxidizing bacteria (AOB) and archaea (AOA) to process N and emit N gases, predicting whether shifts in precipitation may alter NO and N 2 O emissions requires understanding how both AOA and AOB may respond. Thus, we ask: How does altering summer and winter precipitation affect nitrifier‐derived N trace gas emissions in a dryland ecosystem? To answer this question, we manipulated summer and winter precipitation and measured AOA‐ and AOB‐derived N trace gas emissions, AOA and AOB abundance, and soil N concentrations. We found that excluding summer precipitation increased AOB‐derived NO emissions, consistent with the increase in soil N availability, and that increasing summer precipitation amount promoted AOB activity. Excluding precipitation in the winter (the most extreme water limitation we imposed) did not alter nitrifier‐derived NO emissions despite N accumulating in soils. Instead, nitrate that accumulated under drought correlated with high N 2 O emission via denitrification upon wetting dry soils. Increases in the timing and intensity of precipitation that are forecasted under climate change may, therefore, influence the emission of N gases according to the magnitude and season during which the changes occur.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Artificial Light Increases Nighttime Prevalence of Predatory Fishes, Altering Community Composition on Coral Reefs - Emma Weschke; Jules Schligler; Isla Hely; Thibaut Roost; Jo‐Ann Schies; Ben Williams; Bartosz Dworzanski; Suzanne C. Mills; Ricardo Beldade; Stephen D. Simpson; Andrew N. Radford (Global Change Biology, 2024)
Artificial light at night (ALAN) is an anthropogenic pollutant that is intensifying and expanding in marine environments, but experimental studies of community‐level effects are generally lacking. The inshore, shallow, and clear‐water locations of coral reefs and their diverse photosensitive inhabitants make these ecosystems highly susceptible to biological disturbances; at the same time, their biodiversity and accessibility make them model systems for wider insight. Here, we experimentally manipulated ALAN using underwater LED lights on a Polynesian reef system to investigate the influence on localised nighttime fish communities compared to control sites without ALAN. We collected infrared video censuses of baseline communities prior to manipulation, which we repeated following short‐term (mean of three nights) and prolonged (mean of 25 nights) exposures to ALAN. Short‐term ALAN exposure did not induce any significant alterations to the nighttime fish community, but prolonged ALAN exposure increased nighttime species richness. Species compositions exposed to prolonged ALAN were more dissimilar from their baseline compared to control sites. The difference between community compositions at prolonged ALAN exposure and control sites was not apparent at the family level; instead, it was observed from the composition of trait guilds. Following prolonged ALAN exposure, more diurnal and nocturnal predatory species (piscivores, invertivores, and planktivores)—particularly those that are site‐attached or mobile within reefs—were present in nighttime assemblages. Our experimental findings show that coastal ALAN could cause trophic imbalances and circadian disturbances in localised nighttime reef fish communities. Given that community‐wide consequences were only apparent after prolonged ALAN exposure suggests that management of the duration of artificial lighting could potentially be used to reduce impacts on marine ecosystems.

Early-stage outcomes and cost-effectiveness of implementing tourism-led coral propagation and outplanting in the Whitsundays (Great Barrier Reef) - Rachael Scott; David Suggett; Cassidy Hayward; Brent Chatterton; John Edmondson; Johnny Gaskell; Gemma M. Gillette; Lorna Howlett; Emily Monacella; Christine D. Roper; Paige Strudwick; James Unsworth; et al. (Frontiers in Marine Science, 2024)
Implementation of coral restoration practices within reef management strategies is accelerating globally to support reef resilience and recovery. However, full costs underpinning restoration project feasibility have historically been underreported yet are critical to informing restoration cost-benefit decision-making. Such knowledge is especially lacking for Australia’s Great Barrier Reef (GBR), where a coral restoration program led by reef tourism operators, Coral Nurture Program (CNP), was initiated in 2018 (northern GBR) and continues to scale. Here we describe the early outcomes and costs of implementing similar tourism-led asexual coral propagation and outplanting practices in a new region, the Whitsundays (central GBR) through the CNP. Specifically, we detail the local operational and environmental context of CNP Whitsundays, describe the costs of implementation and continuation of restoration activities, as well as evaluate survivorship of coral outplants across three restoration sites for nine months after project establishment (August 2022 to June 2023). Baseline benthic surveys revealed relatively low hard coral cover at restoration sites (ranging from 3.22-8.67%), which significantly differed in benthic composition from coral collection sites (ranging 16.67-38.06%), supporting strong motivation by tourism operators to undertake restoration activities. Mean coral survivorship of coral outplants in fate-tracked plots differed between the three restoration sites after 267 days (ranging 23.33-47.58%), with declines largely driven by coral detachment. Early-stage cost-effectiveness (costs relative to outplant survival) associated with implementation of restoration activity varied widely from US$33.04-178.55 per surviving coral (n = 4,425 outplants) depending on whether ‘in-kind’ costs, restoration activity (outplanting only vs. total costs encompassing planning through to monitoring), site-based survivorship, or a combination of these factors, were considered. As coral reef restoration projects continue to be established globally, our results highlight the need for ongoing, long-term monitoring that can inform adaptive practice, and fully transparent cost-reporting to understand and improve feasibility for any given project. We further highlight the inherent context-dependency of restoration costs, and the importance of considering local social-environmental contexts and their associated cost-benefits in economic rationale for reef restoration projects.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Nitrifier controls on soil NO and N2O emissions in three chaparral ecosystems under contrasting atmospheric N inputs - Alexander H. Krichels; Aral C. Greene; Elizah Z. Stephens; Sharon Zhao; Joshua P. Schimel; Emma L. Aronson; Erin J. Hanan; Peter M. Homyak (Soil Biology and Biochemistry, 2024)

Recreational fisheries-related injuries and body size affect travel rate and post-release mortality in marine migrating coho salmon (Oncorhynchus kisutch) - Emma L. Lunzmann-Cooke; Scott G. Hinch; Arthur L. Bass; Stephen D. Johnston; Brian J. Hendriks; Aswea D. Porter; Steven J. Cooke; David W. Welch (Fisheries Research, 2024)

Does ‘portion size’ matter? Brain responses to food and non-food cues presented in varying amounts - Bari A. Fuchs; Alaina L. Pearce; Barbara J. Rolls; Stephen J. Wilson; Emma Jane Rose; Charles F. Geier; Kathleen L. Keller (Appetite, 2024)

Influence of acute dietary nitrate supplementation timing on nitrate metabolism, central and peripheral blood pressure and exercise tolerance in young men - Samantha N. Rowland; Lewis J. James; Emma O’Donnell; Stephen J. Bailey (European Journal of Applied Physiology, 2024)
Purpose Dietary nitrate (NO 3 − ) supplementation can lower systolic blood pressure (SBP) and improve exercise performance. Salivary flow rate (SFR) and pH are key determinants of oral NO 3 − reduction and purported to peak in the afternoon. We tested the hypotheses that NO 3 − -rich beetroot juice (BR) would increase plasma [nitrite] ([NO 2 − ]), lower SBP and improve exercise performance to a greater extent in the afternoon (AFT) compared to the morning (MORN) and evening (EVE). Method Twelve males completed six experimental visits in a repeated-measures, crossover design. NO 3 − -depleted beetroot juice (PL) or BR (~ 13 mmol NO 3 − ) were ingested in the MORN, AFT and EVE. SFR and pH, salivary and plasma [NO 3 − ] and [NO 2 − ], brachial SBP and central SBP were measured pre and post supplementation. A severe-intensity exercise tolerance test was completed to determine cycling time to exhaustion (TTE). Results There were no between-condition differences in mean SFR or salivary pH. The elevation in plasma [NO 2 − ] after BR ingestion was not different between BR-MORN, BR-AFT and BR-EVE. Brachial SBP was unchanged following BR supplementation in all conditions. Central SBP was reduced in BR-MORN (− 3 ± 4 mmHg), BR-AFT (− 4 ± 3 mmHg), and BR-EVE (− 2 ± 3 mmHg), with no differences between timepoints. TTE was not different between BR and PL at any timepoint. Conclusion Acute BR supplementation was ineffective at improving TTE and brachial SBP and similarly effective at increasing plasma [NO 2 − ] and lowering central SBP across the day, which may have implications for informing NO 3 − supplementation strategies.

Climate services for agriculture: Steering towards inclusive innovation in Australian climate services design and delivery - Stephen Snow; Simon Fielke; Aysha Fleming; Emma Jakku; Yuwan Malakar; Charles Turner; Tammy Hunter; Sigrid Tijs; Graham Bonnett (Agricultural Systems, 2024)

A simulation study of extrapolation uncertainty in exposure assessment – Use of pilot study results for site investigation - Philip E. Goodrum; Emma S. Mendelsohn; Stephen M. Roberts; Leah D. Stuchal (Journal of Environmental Management, 2024)

UK flockdown: A survey of smallscale poultry keepers and their understanding of governmental guidance on highly pathogenic avian influenza (HPAI) - Emma McClaughlin; Sol Elliott; Sarah Jewitt; Matthew Smallman-Raynor; Stephen Dunham; Tamsin Parnell; Michael Clark; Rachael Tarlinton (Preventive Veterinary Medicine, 2024)

The development of a novel decision support system for regional land use planning for brownfield land - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Alistair Dick; Drew Hardy; Mark Dickens; Emma Washbourn; Darren J. Beriro (Journal of Environmental Management, 2024)

From data to decisions: Empowering brownfield redevelopment with a novel decision support system - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Alistair Dick; Drew Hardy; Mark Dickens; Emma Washbourn; Darren J. Beriro (Journal of Environmental Management, 2023)

Are transport networks in low-income countries prepared for climate change? Barriers to preparing for climate change in Africa and South Asia - Sarah Greenham; Robin Workman; Kevin McPherson; Emma Ferranti; Rachel Fisher; Stephen Mills; Roger Street; John Dora; Andrew Quinn; Clive Roberts (Mitigation and Adaptation Strategies for Global Change, 2023)
Climate change, through extreme weather events and slow onset climatic changes, disrupts the operation of transport networks, and those in low-income countries (LICs) across Africa and South Asia are particularly vulnerable to climate change. This paper explores the barriers that LICs face across Africa and South Asia regarding preparedness of transport infrastructure to climate change, with the intent of addressing the knowledge gaps and consequential needs of LICs to support the delivery of more climate-resilient transport. Literature on climate change adaptation and transport resilience among LICs is reviewed to identify the broad challenges and barriers regarding climate change adaptation. Semi-structured interviews with 13 transport stakeholders across Africa and South Asia were also conducted to understand the challenges specific to the transport sector in the regions. Several barriers were identified, including a lack of data and knowledge on climate change impacts, design and prioritisation of remedial actions, budgeting and planning for climate change, and identifying and engaging with stakeholders. Findings from this paper and the wider research project it comprises inform policy guidance that calls for greater national and international coordination to develop practical, relevant and usable data, tools, advice and support for some of the most at-risk transport networks to climate change in the world.

Assessing and improving the outcomes of nonpoint source water quality trading policies in urban areas: A case study in Virginia - Linnea Saby; R. Seth Herbst; Jonathan L. Goodall; Jacob D. Nelson; Teresa B. Culver; Emma Stephens; Caroline M. Marquis; Lawrence E. Band (Journal of Environmental Management, 2023)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

Geological controls of discharge variability in the Thames Basin, UK from cross-spectral analyses: Observations versus modelling - Graham P. Weedon; Emma L. Robinson; John P. Bloomfield; Stephen Turner; Emily J. Crane; Martin J. Best (Journal of Hydrology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Examining the Potential Formation of Ternary DNA Complexes with Chromium‑Cysteine, Chromium-Ascorbate, and Chromium-Glutathione and Implications for Their Carcinogenicity - Sydney Marchi; Emma Lankford; Bradley Dorin; Eilidh Drummond; Sumner C. Thomas; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2023)

Three weeks of mental training changes physiological outcomes during a time trial to exhaustion - Timothy A. VanHaitsma; Stephen P. Gonzalez; Sten Kajitani; Emma Gabriano; Gavin E. Hoiosen; Michael C. Oldach; Karly L. Kingsley (European Journal of Applied Physiology, 2023)
Mental training (MT) can increase endurance performance. The purpose of this study was to examine the minimum dose of mental training needed to increase performance and elucidate the physiological mechanisms underlying this improvement. In a randomized between groups pre-test–post-test design, 33 participants visited the lab on 6 separate days. A VO 2peak with ventilatory threshold (VT) was performed on day 1. The subsequent visits consisted of time trials to exhaustion (TTE) performed at 10% above VT. Between visit 3 and 6, the MT group ( n = 16) watched a video for 10–15 min each day for 3 weeks, while the control group (CON; n = 17) did no mental training. Heart rate (HR), rate of perceived exertion (RPE), VAS scores for pain and fatigue, electromyography, and metabolic and neuromuscular data were collected and recorded during the time trials. The GRIT-S and CD-RISC 10 surveys were completed before study days 3 and 6. TTE increased significantly for MT beginning after 2 weeks (10.0 ± 13.1%) with no further change after 3 weeks (10.4 ± 13.2). TTE also significantly decreased during the last TTE for CON (−10.3 ± 12.7). VO 2 , ventilation, and frequency of breathing were significantly reduced in the latter stages of the TTE for MT. EMG was also significantly decreased for MT as compared for CON throughout the trial. Three weeks of mental training improves performance by reducing EMG, decreasing activation of the muscle and reducing metabolic factors during the latter stages of exercise.

Children with lower ratings of executive functions have a greater response to the portion size effect - Kathleen L. Keller; Alaina L. Pearce; Bari Fuchs; Kyle Hallisky; Barbara J. Rolls; Stephen J. Wilson; Charles Geier; Emma J. Rose (Appetite, 2023)

The phytotoxicity of soil-applied herbicides is enhanced in the first-year post strategic deep tillage - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Mick Rose; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2023)

Rate of Adverse Outcomes During 6-Hour Observation for Asymptomatic Patients with Select Ingestions - Michael Keenan; Stephen Rice; Emma Frawley; Chelsie Jacques; Susan Wojcik; Jeanna Marraffa (Journal of Medical Toxicology, 2023)

Sex differences in estimates of cardiac autonomic function using heart rate variability: effects of dietary capsaicin - Kendall S. Zaleski; Abena O. Gyampo; Brian Lora; Tawn Tomasi; Meaghan Lynch; Gaia Giuriato; Emma Basso; Emma Finegan; Jack Schickler; Massimo Venturelli; Justin DeBlauw; Stephen J. Ives (European Journal of Applied Physiology, 2023)

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

From backyards to the backcountry: Exploring outdoor recreation coping strategies and experiences during the 2020 COVID-19 pandemic in New Zealand - Niamh Espiner; Gebeyaw Degarege; Emma J. Stewart; Stephen Espiner (Journal of Outdoor Recreation and Tourism, 2023)

News media and fisheries-independent data reveal hidden impacts of hurricanes - Stephen F. Jane; Kayla M. Smith; Dana Baker; Allison Saroni; Emma Cutler; Paul Carvalho (Ambio, 2022)

Localized Native American impacts on past forest composition across a regional extent in north‐eastern United States - Stephen J. Tulowiecki; Emma R. Ranney; Emily M. Keenan; Gabrielle M. Neubert; Marcie L. Hogan (Journal of Biogeography, 2022)
Aim Researchers have debated impacts of past Native American land use on forests including upon tree species composition in north‐eastern United States (US), with estimates of impacts ranging from local to regional extent. This study examines tree relative abundances to assess whether Native Americans influenced geographic distributions prior to Euro‐American settlement. Location North‐eastern United States (approx. 420,000 km 2 ). Taxon Ash ( Fraxinus spp.), basswood ( Tilia americana ), beech ( Fagus grandifolia ), birch ( Betula spp.), cherry ( Prunus spp.), chestnut ( Castanea dentata ), dogwood ( Cornus spp.), elm ( Ulmus spp.), fir ( Abies balsamea ), hemlock ( Tsuga canadensis ), hickory ( Carya spp.), ironwood ( Carpinus caroliniana and Ostrya virginiana ), maple ( Acer spp.), oak ( Quercus spp.), pine ( Pinus spp.), spruce ( Picea spp.), tamarack ( Larix laricina ) and walnut ( Juglans spp.), Methods We used boosted regression trees to model abundance patterns and to assess the importance of distance‐based proxies of Native American land use versus environmental variables. We trained models that included and excluded distance‐based proxies. Abundance estimates from original land survey records (1650–1850 CE) were acquired for taxa at 8 km spatial resolution, and related to Native American settlement locations (1500–1800 CE) and 27 environmental variables. Results When evaluated upon test data, regional‐scale models of relative abundance that included distance‐based proxies performed only slightly better than models that excluded them, with mean improvements in RMSE of 0.1 percentage points. Models suggest that Native American land use modestly altered the relative abundance of taxa locally, extending no more than 50 km from settlement. Models also suggest slight increases near settlement of a few percentage points in relative abundance for fire‐tolerant and/or dietary taxa (e.g. oak, hickory and pine), and for early‐successional taxa (e.g. ash). Main conclusions Past Native American land use had no detectable effect on forest composition across a regional extent, but increased the abundance of fire‐tolerant, shade‐intolerant and nut‐producing trees locally.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Examining the Potential Formation of Ternary Chromium-Histidine-DNA Complexes and Implications for Their Carcinogenicity - Emma Lankford; C. Sumner Thomas; Sydney Marchi; Silas Brown; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2022)

Stream Water Chemistry in Mixed-Conifer Headwater Basins: Role of Water Sources, Seasonality, Watershed Characteristics, and Disturbances - Yang Yang; Stephen C. Hart; Emma P. McCorkle; Erin M. Stacy; Morgan E. Barnes; Carolyn T. Hunsaker; Dale W. Johnson; Asmeret Asefaw Berhe (Ecosystems, 2021)

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Public Perceptions of the Ocean: Lessons for Marine Conservation From a Global Research Review - Rebecca Jefferson; Emma McKinley; Holly Griffin; Alison Nimmo; Stephen Fletcher (Frontiers in Marine Science, 2021)
Insights into how public audiences perceive and relate to the ocean are pivotal to successful societal engagement and integration of human dimensions in marine conservation. Perceptions research explores how people understand, value or engage with an environment, issue or management response, and in the context of marine conservation, provides crucial insights for the development, delivery and evaluation of effective conservation interventions. This review of 349 peer reviewed studies explores the current state of research into public perceptions of the ocean. Using an extensive data extraction process, the review examined the geographical spread of ocean perceptions research, the topics of research focus, and the methods used. The review identifies gaps in current research activity, and opportunities for maximizing the impact of ocean perceptions research in current and future marine conservation. Key findings of the review include evidence that the rate of research is growing, with 59% of studies published between 2013–2017. However, a clear geographical skew is evident, with the majority of studies being undertaken in higher income countries. Furthermore, there has been a tendency to focus on charismatic species, or issues and spaces of clear human-ocean interaction (e.g., beaches), highlighting significant gaps in the topics and themes currently covered by ocean perceptions research. An additional gap identified is the underutilization of available methods to explore the complexity of marine perceptions. In a bid to address these gaps, the paper concludes with a series of recommendations designed to stimulate and support ocean perceptions research as being fundamental to the success of marine conservation efforts. While ocean perceptions research may be young, the growing research effort evidenced in this review gives optimism for realizing its potential and continuing to improve the integration of ocean perceptions research effectively into marine conservation.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Annotation of immune genes in the extinct thylacine (Thylacinus cynocephalus) - Emma Peel; Stephen Frankenberg; Carolyn J. Hogg; Andrew Pask; Katherine Belov (Immunogenetics, 2021)

Family history of prostate cancer and prostate tumor aggressiveness in black and non-black men;results from an equal access biopsy study - Kimberly R. Jenkins; Taofik Oyekunle; Lauren E. Howard; Emily K. Wiggins; Stephen J. Freedland; Emma H. Allott (Cancer Causes & Control, 2021)
Purpose To test for racial differences in associations between family history (FH) of prostate cancer (PC) and prostate cancer aggressiveness in a racially diverse equal access population undergoing prostate biopsy. Subjects/patients and methods We prospectively enrolled men undergoing prostate biopsy at the Durham Veterans Administration from 2007 to 2018 and assigned case or control status based on biopsy results. Race and FH of PC were self-reported on questionnaires. Logistic regression was used to test the association between FH and PC diagnosis overall and by tumor aggressiveness [high- (Grade Group 3–5) or low-grade (Grade Group 1–2) vs. no cancer], overall, and stratified by race. Models were adjusted for age and year of consent, race, PSA level, digital rectal exam findings, prostate volume, and previous (negative) biopsy receipt. Results Of 1,225 men, 323 had a FH of PC and 652 men were diagnosed with PC on biopsy. On multivariable analysis, FH was associated with increased odds of high-grade PC in black (OR 1.85, p = 0.041) and all men (OR 1.56, p = 0.057) and was unrelated to overall or low-grade PC diagnosis, overall, or stratified by race (all p ≥ 0.325). In sensitivity analyses among men without a previous biopsy, results were slightly more pronounced. Conclusion In this setting of equal access to care, positive FH of PC was associated with increased tumor aggressiveness in black men, but not non-black men undergoing prostate biopsy. Further research is required to tease apart the contribution of genetics from increased PC awareness potentially influencing screening and biopsy rates in men with FH.

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Fibulin-3 knockout mice demonstrate corneal dysfunction but maintain normal retinal integrity - Steffi Daniel; Marian Renwick; Viet Q. Chau; Shyamtanu Datta; Prabhavathi Maddineni; Gulab Zode; Emma M. Wade; Stephen P. Robertson; W. Matthew Petroll; John D. Hulleman (Journal of Molecular Medicine, 2020)

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Feeding Biomechanics Influences Craniofacial Morphology at the Subspecies Scale among Australian Pademelons (Macropodidae: Thylogale) - D. Rex Mitchell; Emma Sherratt; Gabriele Sansalone; Justin A. Ledogar; Richard J. Flavel; Stephen Wroe (Journal of Mammalian Evolution, 2020)

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress - Emma F. Camp; Tim Kahlke; Matthew R. Nitschke; Deepa Varkey; Nerissa L. Fisher; Lisa Fujise; Samantha Goyen; David J. Hughes; Caitlin A. Lawson; Mickael Ros; Stephen Woodcock; Kun Xiao; et al. (Environmental Microbiology, 2020)
Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.

Differential rearing alters taste reactivity to ethanol, sucrose, and quinine - Thomas J. Wukitsch; Emma C. Brase; Theodore J. Moser; Stephen W. Kiefer; Mary E. Cain (Psychopharmacology, 2020)

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

Quantifying the legacy of snowmelt timing on soil greenhouse gas emissions in a seasonally dry montane forest - Joseph C. Blankinship; Emma P. McCorkle; Matthew W. Meadows; Stephen C. Hart (Global Change Biology, 2018)
The release of water during snowmelt orchestrates a variety of important belowground biogeochemical processes in seasonally snow‐covered ecosystems, including the production and consumption of greenhouse gases (GHGs) by soil microorganisms. Snowmelt timing is advancing rapidly in these ecosystems, but there is still a need to isolate the effects of earlier snowmelt on soil GHG fluxes. For an improved mechanistic understanding of the biogeochemical effects of snowmelt timing during the snow‐free period, we manipulated a high‐elevation forest that typically receives over two meters of snowfall but little summer precipitation to influence legacy effects of snowmelt timing. We altered snowmelt rates for two years using black sand to accelerate snowmelt and white fabric to postpone snowmelt, thus creating a two‐ to three‐week disparity in snowmelt timing. Soil microclimate and fluxes of carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) were monitored weekly to monthly during the snow‐free period. Microbial abundances were estimated by potential assays near the end of each snow‐free period. Although earlier snowmelt caused soil drying, we found no statistically significant effects ( p 2 or N 2 O, or soil microbial abundances. Soil CH 4 fluxes, however, did respond to snowmelt timing, with 18% lower rates of CH 4 uptake in the earlier snowmelt treatment, but only after a dry winter. Cumulative CO 2 emission and CH 4 uptake were 43% and 88% greater, respectively, after the dry winter. We conclude that soil GHG fluxes can be surprisingly resistant to hydrological changes associated with earlier snowmelt, likely because of persistent moisture and microbial activities in deeper mineral soils. As a result, a drier California in the future may cause seasonally snow‐covered soils in the Sierra Nevada to emit more GHGs, not less.

Experimentally manipulating light spectra reveals the importance of dark corridors for commuting bats - Matt R. K. Zeale; Emma L. Stone; Emma Zeale; William J. Browne; Stephen Harris; Gareth Jones (Global Change Biology, 2018)
The rapid global spread of artificial light at night is causing unprecedented disruption to ecosystems. In otherwise dark environments, street lights restrict the use of major flight routes by some bats, including the threatened lesser horseshoe bat Rhinolophus hipposideros , and may disrupt foraging. Using radio tracking, we examined the response of individual female R. hipposideros to experimental street lights placed on hedgerows used as major flight routes. Hedgerows were illuminated on one side over four nights using lights with different emission spectra, while the opposite side of the hedge was not illuminated. Automated bat detectors were used to examine changes in overall bat activity by R. hipposideros and other bat species present. R. hipposideros activity reduced significantly under all light types, including red light, challenging a previously held assumption that red light is safe for bats. Despite this, R. hipposideros rapidly adapted to the presence of lights by switching their flight paths to the dark side of the hedgerow, enabling them to reach foraging sites without restriction. Red light had no effect on the activity of the other species present. Slow‐flying Myotis spp. avoided orange, white and green light, while more agile Pipistrellus spp. were significantly more active at these light types compared to dark controls, most probably in response to accumulations of insect prey. No effect of any light type was found for Nyctalus or Eptesicus spp. Our findings demonstrate that caution must be used when promoting forms of lighting that are thought to be safe for wildlife before they are tested more widely. We argue that it is essential to preserve dark corridors to mitigate the impacts of artificial light at night on bat activity and movements.

Staphylococcus aureus colonisation and its relationship with skin and soft tissue infection in New Zealand children - Mark R. Hobbs; Cameron C. Grant; Mark G. Thomas; Sarah Berry; Susan M. B. Morton; Emma Marks; Stephen R. Ritchie (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Size-dependent variability in the formation and trade-offs of facultative aggregations in golden orb-web spiders (Nephila clavipes) - Elise Ferree; Stephen Johnson; Daniella Barraza; Emma Crabo; Jenna Florio; Haley Godtfredsen; Kennedy Holland; Kanyarat Jitmana; Kaya Mark (Behavioral Ecology and Sociobiology, 2018)

The determination of monomers and oligomers from polyester-based can coatings into foodstuffs over extended storage periods - Malcolm Driffield; Monica Garcia-Lopez; Julie Christy; Antony Stephen Lloyd; Jonathan Andrew Tarbin; Patrick Hough; Emma Louise Bradley; Peter Kenneth Thomas Oldring (Food Additives & Contaminants: Part A, 2018)

Plant controls on Late Quaternary whole ecosystem structure and function - Elizabeth S. Jeffers; Nicki J. Whitehouse; Adrian Lister; Gill Plunkett; Phil Barratt; Emma Smyth; Philip Lamb; Michael W. Dee; Stephen J. Brooks; Katherine J. Willis; Cynthia A. Froyd; Jenny E. Watson; et al. (Ecology Letters, 2018)
Plants and animals influence biomass production and nutrient cycling in terrestrial ecosystems; however, their relative importance remains unclear. We assessed the extent to which mega‐herbivore species controlled plant community composition and nutrient cycling, relative to other factors during and after the Late Quaternary extinction event in Britain and Ireland, when two‐thirds of the region's mega‐herbivore species went extinct. Warmer temperatures, plant–soil and plant–plant interactions, and reduced burning contributed to the expansion of woody plants and declining nitrogen availability in our five study ecosystems. Shrub biomass was consistently one of the strongest predictors of ecosystem change, equalling or exceeding the effects of other biotic and abiotic factors. In contrast, there was relatively little evidence for mega‐herbivore control on plant community composition and nitrogen availability. The ability of plants to determine the fate of terrestrial ecosystems during periods of global environmental change may therefore be greater than previously thought.

The century experiment: the first twenty years of UC Davis' Mediterranean agroecological experiment - Kristina M. Wolf; Emma E. Torbert; Dennis Bryant; Martin Burger; R. Ford Denison; Israel Herrera; Jan Hopmans; Will Horwath; Stephen Kaffka; Angela Y. Y. Kong; R. F. Norris; Johan Six; et al. (Ecology, 2018)
The Century Experiment at the Russell Ranch Sustainable Agriculture Facility at the University of California, Davis provides long‐term agroecological data from row crop systems in California's Central Valley starting in 1993. The Century Experiment was initially designed to study the effects of a gradient of water and nitrogen availability on soil properties and crop performance in ten different cropping systems to measure tradeoffs and synergies between agricultural productivity and sustainability. Currently systems include 11 different cropping systems–consisting of four different crops and a cover crop mixture–and one native grass system. This paper describes the long‐term core data from the Century Experiment from 1993–2014, including crop yields and biomass, crop elemental contents, aerial‐photo‐based Normalized Difference Vegetation Index data, soil properties, weather, chemical constituents in irrigation water, winter weed populations, and operational data including fertilizer and pesticide application amounts and dates, planting dates, planting quantity and crop variety, and harvest dates. This data set represents the only known long‐term set of data characterizing food production and sustainability in irrigated and rainfed Mediterranean annual cropping systems. There are no copyright restrictions associated with the use of this dataset.

Coral Community Structure and Recruitment in Seagrass Meadows - Kathryn E. Lohr; David J. Smith; David J. Suggett; Matthew R. Nitschke; Alex J. Dumbrell; Stephen Woodcock; Emma F. Camp (Frontiers in Marine Science, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Erratum to: Temperature and human thermal comfort effects of street trees across three contrasting street canyon environments - Andrew M. Coutts; Emma C. White; Nigel J. Tapper; Jason Beringer; Stephen J. Livesley (Theoretical and Applied Climatology, 2016)

How many conservation units are there for the endangered grassland earless dragons? - Emma Carlson; Anna J. MacDonald; Aaron Adamack; Tim McGrath; Lisa I. Doucette; William S. Osborne; Bernd Gruber; Stephen D. Sarre (Conservation Genetics, 2016)

Adaptation and development trade-offs: fluvial sediment deposition and the sustainability of rice-cropping in An Giang Province, Mekong Delta - Alexander D. Chapman; Stephen E. Darby; Hoàng M. Hồng; Emma L. Tompkins; Tri P. D. Van (Climatic Change, 2016)

Harold Edwin Hurst: the Nile and Egypt, past and future - John Sutcliffe; Stephen Hurst; Ayman G. Awadallah; Emma Brown; Khaled Hamed (Hydrological Sciences Journal, 2016)

Temperature and human thermal comfort effects of street trees across three contrasting street canyon environments - Andrew M. Coutts; Emma C. White; Nigel J. Tapper; Jason Beringer; Stephen J. Livesley (Theoretical and Applied Climatology, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Diverse phenotypic consequences of mutations affecting the C-terminus of FLNA - Margriet van Kogelenberg; Alice R. Clark; Zandra Jenkins; Tim Morgan; Ananda Anandan; Gregory M. Sawyer; Matthew Edwards; Tracy Dudding; Tessa Homfray; Bruce Castle; John Tolmie; Fiona Stewart; et al. (Journal of Molecular Medicine, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Late glacial and Holocene environmental changes inferred from sediments in Lake Myklevatnet, Nordfjord, western Norway - Atle Nesje; Jostein Bakke; Stephen J. Brooks; Darrell S. Kaufman; Emma Kihlberg; Mathias Trachsel; William J. D’Andrea; John A. Matthews (Vegetation History and Archaeobotany, 2014)

Sources of Variation in Cuticular Hydrocarbons in the Ant Formica exsecta - Stephen J. Martin; Emma Vitikainen; Sue Shemilt; Falko P. Drijfhout; Liselotte Sundström (Journal of Chemical Ecology, 2013)

Mitigating the Effect of Development on Bats in England with Derogation Licensing - EMMA LOUISE STONE; GARETH JONES; STEPHEN HARRIS (Conservation Biology, 2013)
The Convention on Biological Diversity has catalyzed worldwide awareness of threats to biological diversity and stimulated global conservation strategies. These have led to national and international legislation and have generated debate about the most effective conservation actions. Under the EU Habitats Directive, all member states are obliged to establish a system for strict protection of species listed in Annex IV(a), which includes all bats. In England, this obligation has resulted in legislation that allows for derogation from strict protection under license, provided activities are undertaken to mitigate any potential negative effects on bat numbers. We used an evidence‐based approach to assess the cost‐effectiveness of mitigation strategies and the English bat‐derogation licensing process as a whole. We analyzed data from 389 bat derogation licenses issued in England from 2003 to 2005 relating to 1776 roosts and 15 species to determine the nature and extent of development and mitigation activities and their effects on bats. Overall the effects of licensed activities on roosts were negative. Despite the level of protection afforded to bats, the majority (68%) of roosts for which derogation licenses were issued were destroyed. There were species‐specific differences in the probability of roosts being destroyed, and impacts on roosts did not reflect a species’ conservation status. Information provided by licensees was inadequate and inconsistent. Most licensees (67%) failed to submit postdevelopment reports, and postdevelopment monitoring was conducted at only 19% of sites. Despite a minimum of £4.13 million spent on mitigation structures for bats from 2003 to 2005, it was unclear whether the licensing process meets EU obligations. On the basis of our results, we believe there is a need to overhaul the licensing process, to establish a comprehensive, standardized postdevelopment monitoring system, and to demonstrate that mitigation is commensurate with Britain's legal obligations. Mitigando el Efecto del Desarrollo sobre los Murciélagos en Inglaterra con Licencias de Derogación

Combined walking exercise and alkali therapy in patients with CKD4–5 regulates intramuscular free amino acid pools and ubiquitin E3 ligase expression - Emma L. Watson; George C. Kosmadakis; Alice C. Smith; Joao L. Viana; Jeremy R. Brown; Karen Molyneux; Izabella Z. A. Pawluczyk; Michael Mulheran; Nicolette C. Bishop; Susan Shirreffs; Ronald J. Maughan; Paul J. Owen; et al. (European Journal of Applied Physiology, 2013)

Phylogeography and postglacial recolonization of Europe by Rhinolophus hipposideros : evidence from multiple genetic markers - Serena E. Dool; Sébastien J. Puechmaille; Christian Dietz; Javier Juste; Carlos Ibáñez; Pavel Hulva; Stéphane G. Roué; Eric J. Petit; Gareth Jones; Danilo Russo; Roberto Toffoli; Andrea Viglino; et al. (Molecular Ecology, 2013)
The demographic history of Rhinolophus hipposideros (lesser horseshoe bat) was reconstructed across its European, North African and Middle‐Eastern distribution prior to, during and following the most recent glaciations by generating and analysing a multimarker data set. This data set consisted of an X‐linked nuclear intron (Bgn; 543 bp), mitochondrial DNA (cytb‐ tRNA ‐control region; 1630 bp) and eight variable microsatellite loci for up to 373 individuals from 86 localities. Using this data set of diverse markers, it was possible to determine the species’ demography at three temporal stages. Nuclear intron data revealed early colonization into Europe from the east, which pre‐dates the Quaternary glaciations. The mtDNA data supported multiple glacial refugia across the Mediterranean, the largest of which were found in the Ibero‐Maghreb region and an eastern location (Anatolia/Middle East)–that were used by R. hipposideros during the most recent glacial cycles. Finally, microsatellites provided the most recent information on these species’ movements since the Last Glacial Maximum and suggested that lineages that had diverged into glacial refugia, such as in the Ibero‐Maghreb region, have remained isolated. These findings should be used to inform future conservation management strategies for R. hipposideros and show the power of using a multimarker data set for phylogeographic studies.

16 S rRNA survey revealed complex bacterial communities and evidence of bacterial interference on human adenoids - Tiantian Ren; Dominique Ulrike Glatt; Tam Nhu Nguyen; Emma Kaitlynn Allen; Stephen V. Early; Michele Sale; Birgit Winther; Martin Wu (Environmental Microbiology, 2013)
Summary Adenoid microbiota plays an important role in the development of various infectious and non‐infectious diseases of the upper airways, such as otitis media, adenotonsillitis, rhinosinusitis and adenoid hypertrophy. Studies have suggested that adenoids could act as a potential reservoir of opportunistic pathogens. However, previous bacterial surveys of adenoids were mainly culture based and therefore might only provide an incomplete and potentially biased assessment of the microbial diversity. To develop an in‐depth and comprehensive understanding of the adenoid microbial communities and test the ‘pathogen reservoir hypothesis’, we carried out a 16 S rRNA based, culture‐independent survey of bacterial communities on 67 human adenoids removed by surgery. Our survey revealed highly diverse adenoid bacterial communities distinct from those of other body habitats. Despite large interpersonal variations, adenoid microbiota shared a core set of taxa and can be classified into at least five major types based on its bacterial species composition. Our results support the ‘pathogen reservoir hypothesis’ as we found common pathogens of otitis media to be both prevalent and abundant. Co‐occurrence analyses revealed evidence consistent with the bacterial interference theory in that multiple common pathogens showed ‘non‐coexistence’ relationships with non‐pathogenic members of the commensal microflora.

“Modeling the impact of natural resource-based poverty traps on food security in Kenya: The Crops, Livestock and Soils in Smallholder Economic Systems (CLASSES) model” - Emma C. Stephens; Charles F. Nicholson; Douglas R. Brown; David Parsons; Christopher B. Barrett; Johannes Lehmann; David Mbugua; Solomon Ngoze; Alice N. Pell; Susan J. Riha (Food Security, 2012)

Conserving energy at a cost to biodiversity? Impacts of LED lighting on bats - Emma L. Stone; Gareth Jones; Stephen Harris (Global Change Biology, 2012)
Artificial lighting is a key biodiversity threat and produces 1900 million tonnes of CO 2 emissions globally, more than three times that produced by aviation. The need to meet climate change targets has led to a global increase in energy‐efficient light sources such as high‐brightness light‐emitting diodes ( LED s). Despite the energetic benefits of LED s, their ecological impacts have not been tested. Using an experimental approach, we show that LED street lights caused a reduction in activity of slow‐flying bats ( R hinolophus hipposideros and M yotis spp.). Both R . hipposideros and M yotis spp. activities were significantly reduced even during low light levels of 3.6 lux. There was no effect of LED lighting on the relatively fast‐flying P ipistrellus pipistrellus , P ipistrellus pygmaeus and N yctalus/ E ptesicus spp. We provide the first evidence of the effects of LED lights on bats. Despite having considerable energy‐saving benefits, LED lights can potentially fragment commuting routes for bats with associated negative conservation consequences. Our results add to the growing evidence of negative impacts of lighting on a wide range of taxa. We highlight the complexities involved in simultaneously meeting targets for reduction of greenhouse gas emissions and biodiversity loss. New lighting strategies should integrate climate change targets with the cultural, social and ecological impacts of emerging lighting technologies.

Genome‐wide analysis of longevity in nutrient‐deprived Saccharomyces cerevisiae reveals importance of recycling in maintaining cell viability - Hazel M. Davey; Emma J. M. Cross; Christopher, L. Davey; Konstantinos Gkargkas; Daniela Delneri; David C. Hoyle; Stephen G. Oliver; Douglas B. Kell; Gareth W. Griffith (Environmental Microbiology, 2012)
Summary Although typically cosseted in the laboratory with constant temperatures and plentiful nutrients, microbes are frequently exposed to much more stressful conditions in their natural environments where survival and competitive fitness depend upon both growth rate when conditions are favourable and on persistence in a viable and recoverable state when they are not. In order to determine the role of genetic heterogeneity in environmental fitness we present a novel approach that combines the power of fluorescence‐activated cell sorting with barcode microarray analysis and apply this to determining the importance of every gene in the Saccharomyces cerevisiae genome in a high‐throughput, genome‐wide fitness screen. We have grown > 6000 heterozygous mutants together and exposed them to a starvation stress before using fluorescence‐activated cell sorting to identify and isolate those individual cells that have not survived the stress applied. Barcode array analysis of the sorted and total populations reveals the importance of cellular recycling mechanisms (autophagy, pexophagy and ribosome breakdown) in maintaining cell viability during starvation and provides compelling evidence for an important role for fatty acid degradation in maintaining viability. In addition, we have developed a semi‐batch fermentor system that is a more realistic model of environmental fitness than either batch or chemostat culture. Barcode array analysis revealed that arginine biosynthesis was important for fitness in semi‐batch culture and modelling of this regime showed that rapid emergence from lag phase led to greatly increased fitness. One hundred and twenty‐five strains with deletions in unclassified proteins were identified as being over‐represented in the sorted fraction, while 27 unclassified proteins caused a haploinsufficient phenotype in semi‐batch culture. These methods thus provide a screen to identifying other genes and pathways that have a role in maintaining cell viability.

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Identification of coincident QTL for days to heading, spike length and spikelets per spike in Lolium perenne L. - Stephen Byrne; Emma Guiney; Susanne Barth; Iain Donnison; Luis A. J. Mur; Dan Milbourne (Euphytica, 2009)

Animal models of Parkinson’s disease and L-dopa induced dyskinesia: How close are we to the clinic? - Emma Lane; Stephen Dunnett (Psychopharmacology, 2008)

Human stem cells for CNS repair - Rike Zietlow; Emma L. Lane; Stephen B. Dunnett; Anne E. Rosser (Cell and Tissue Research, 2008)

Molecular Evolution of Cytochrome c Oxidase in High-Performance Fish (Teleostei: Scombroidei) - Anne C. Dalziel; Christopher D. Moyes; Emma Fredriksson; Stephen C. Lougheed (Journal of Molecular Evolution, 2006)

Contribution of 5′- and 3′-untranslated regions of plastid mRNAs to the expression of Chlamydomonas reinhardtii chloroplast genes - Dwight Barnes; Scott Franklin; Jason Schultz; Ryan Henry; Emma Brown; Anna Coragliotti; Stephen P. Mayfield (Molecular Genetics and Genomics, 2005)

Estimating domain orientation of two human antibody IgG4 chimeras by crystallohydrodynamics - Emma Longman; Katja Kreusel; Saul B. Tendler; Immo Fiebrig; Kevin King; John Adair; Paul O'Shea; Alvaro Ortega; Jose Garcia de la Torre; Stephen E. Harding (European Biophysics Journal, 2003)